Static output feedback for partial eigenstructure assignment of undamped vibration systems. (February 2016) - Zhang, Jiafan; Ye, Jianping; Ouyang, Huajiang
Abstract: A novel method for partial eigenstructure assignment of undamped vibration systems using acceleration and displacement output feedback is presented in this paper. It is based on modifications of mass and stiffness that preserve partial eigenstructure. A numerical algorithm for determining the required control gain matrices of acceleration and displacement output feedback, which assign the desired eigenstructure, is developed. This algorithm is easy to implement, and works directly on the second-order system model. More importantly, the algorithm allows the output matrix and the input matrix to be specified beforehand and also leads naturally to a small norm solution of the gain matrices. Finally, some numerical results are presented to demonstrate the effectiveness and accuracy of the proposed algorithm. Highlights: Partial eigenstructure assignment of undamped vibration systems by output feedback is addressed. The algorithm allows the input and the output matrix to be specified beforehand. The algorithm mainly involves numerically stable matrix computations. The acceleration and displacement output feedback is concerned.